Arbeitsgemeinschaft über Korrespondenztheorie: 27. bis 30. Januar 1968 - Roquette, Peter (Tagungsbericht, 1968)
G. Frey, Heidelberg; W. D. Geyer, Heidelberg; H. Göhner, Heidelberg; U. Göhner, Tübingen; P. Hahnel, Heidelberg; K. Irion, Heidelberg; J. Leicht, Heidelberg; F. Lorenz, Heidelberg; G. Martens, Heidelberg; R. Maulbetsch, Tübingen; K. Radbruch, Tübingen; P. Roquette, Heidelberg; W. Schmale, Tübingen; G. Tamme, Hamburg; M. Wolff, Tübingen
Keywords: Konferenzschrift